Litteraturkritik, fankultur og affekt: Trump og Pynchons konspirationslæsere: Trump og Pynchons konspirationslæsere - Dalsgaard, Inger H. (K&K - Kultur og Klasse, 2020)
This article outlines the two cultures in the study of conspiracy culture, where social science disciplines provide one type of approach and cultural studies another. To make a claim for recovering the use of literature in the field, both to bridge the divide, if possible, and to suggest new critical directions for literary studies itself, the article offers a reading of two congruent conspiracy narrations, Donald Trump’s rhetoric and Thomas Pynchon’s novels. Both are examples of ambiguous narration, which may be taken at face value by one reader and invested with hidden significance by another, thus creating two closed-off epistemic bubbles – politically and critically. When critics have not been taking conspiracy fans, which could include esteemed literary figures like Pynchon, seriously, they have been guilty of closed reading. Fans themselves, though equally closed readers technically, offer avenues into affective and co-creative conspiracy readings which are, paradoxically, open to the reparative possibilities literature can have in a politically paranoid society.